3, 4, 5‐Trimethoxy Substitution on an N‐DMBI Dopant with New N‐Type Polymers: Polymer‐Dopant Matching for Improved Conductivity‐Seebeck Coefficient Relationship. (17th November 2021) - Han, Jinfeng; Chiu, Arlene; Ganley, Connor; McGuiggan, Patty; Thon, Susanna M.; Clancy, Paulette; Katz, Howard E.
Abstract: Achieving high electrical conductivity and thermoelectric power factor simultaneously for n‐type organic thermoelectrics is still challenging. By constructing two new acceptor‐acceptor n‐type conjugated polymers with different backbones and introducing the 3, 4, 5‐trimethoxyphenyl group to form the new n‐type dopant 1, 3‐dimethyl‐2‐(3, 4, 5‐trimethoxyphenyl)‐2, 3‐dihydro‐1 H ‐benzo[d]imidazole (TP‐DMBI), high electrical conductivity of 11 S cm −1 and power factor of 32 μW m −1 K −2 are achieved. Calculations using Density Functional Theory show that TP‐DMBI presents a higher singly occupied molecular orbital (SOMO) energy level of −1.94 eV than that of the common dopant 4‐(1, 3‐dimethyl‐2, 3‐dihydro‐1 H ‐benzoimidazol‐2‐yl) phenyl) dimethylamine (N‐DMBI) (−2.36 eV), which can result in a larger offset between the SOMO of dopant and lowest unoccupied molecular orbital (LUMO) of n‐type polymers, though that effect may not be dominant in the present work. The doped polymer films exhibit higher Seebeck coefficient and power factor than films using N‐DMBI at the same doping levels or similar electrical conductivity levels. Moreover, TP‐DMBI doped polymer films offer much higher electron mobility of up to 0.53 cm 2 V −1 s −1 than films with N‐DMBI doping, demonstrating the potential of TP‐DMBI, and 3, 4, 5‐trialkoxy DMBIs more broadly, for high performance n‐type organic thermoelectrics. Abstract : Two n‐type conjugated polymers with different backbones and a n‐type dopant 1, 3‐dimethyl‐2‐(3, 4, 5‐trimethoxyphenyl)‐2, 3‐dihydro‐1 H ‐benzo[d]imidazole (TP‐DMBI) are synthesized, and electron mobility of 0.53 cm 2 V −1 S −1, electrical conductivity of 11 S cm −1 and power factor 32 μW m −1 K −2 for n‐type organic thermoelectrics are achieved by TP‐DMBI doped films, which out‐perform N‐DMBI doped films.